2021
DOI: 10.1021/acs.jcim.0c01303
|View full text |Cite
|
Sign up to set email alerts
|

Light Chain Mutation Effects on the Dynamics of Thrombin

Abstract: Thrombin plays an important role in the process of hemostasis and blood coagulation. Studies in thrombin can help us find ways to treat cancer because thrombin is able to reduce the characteristic hypercoagulability of cancer. Thrombin is composed of two chains, the light chain and the heavy chain. The function of the heavy chain has been largely explored, while the function of the light chain was obscured until several disease-associated mutations in the light chain come to light. In this study, we want to ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(39 citation statements)
references
References 57 publications
(135 reference statements)
1
38
0
Order By: Relevance
“…The top-ranked hydrogen bond, LEU62-GLY189, is located between the 30s loop and the gamma loop. The absence of this bond could explain why these two loops become more flexible in ΔK9 as shown in our previous research . In the (WT, E8K) pair (Figure (b),(c)), all of the top 10 important hydrogen bonds have positive beta values, indicating that E8K has an increased number of hydrogen bonds.…”
Section: Resultsmentioning
confidence: 62%
See 1 more Smart Citation
“…The top-ranked hydrogen bond, LEU62-GLY189, is located between the 30s loop and the gamma loop. The absence of this bond could explain why these two loops become more flexible in ΔK9 as shown in our previous research . In the (WT, E8K) pair (Figure (b),(c)), all of the top 10 important hydrogen bonds have positive beta values, indicating that E8K has an increased number of hydrogen bonds.…”
Section: Resultsmentioning
confidence: 62%
“…We used a 9 Å cutoff distance and a 7.5 Å switching distance for the van der Waals and electrostatic forces. These parameters are the default values in ACEMD3, and the same choice can be seen in a variety of MD simulation studies on several different systems by a variety of investigators as well as in our previous studies of thrombin. …”
Section: Methodsmentioning
confidence: 99%
“…The two-dimensional energy landscapes of the PC1 and PC2 revealed that the WT, W305Y, and W305D systems had one (A), three (B1, B2, and B3), and three (C1, C2, and C3) conformational sub-basins ( Figure 4 ), respectively. We next extracted the structures from these sub-basins and conducted clustering analysis on these structures for each system [ 46 , 47 ]. Then, the representative structure extracted from each sub-basin from the W305Y and W305D mutant systems was aligned with that from the WT system to unravel the detailed conformational changes in the protein domains triggered by the Trp305 mutations.…”
Section: Resultsmentioning
confidence: 99%
“…We used hierarchical clustering (HDBSCAN) to analyze the trajectory and obtained the clustering results of wild-type fascin and mutant fascin. 52,53 The results show that when the residues were mutated, the results of protein clustering became different (Figure S2).…”
Section: Rmsd Analysismentioning
confidence: 99%